Foreign Direct Investment In Indonesia: Economic Growth IKN - Sari, Putri; Maysarah, Siti (Ilomata International Journal of Tax and Accounting, 2024)
IKN is expected to become a sustainable city that will drive the country's economy in Indonesia in the future. This research analyses the correlation amidst foreign direct investment, inflation, and environmental degradation with economic growth in IKN. Therefore, this study aims to examine all variables that affect the economic growth of IKN. Thus, this study provides implications for regulators and policymakers on how to optimize IKN's economic growth in a sustainable manner. This analysis utilizes time series data collected from 38 provinces in Indonesia from 2018 to 2022. Secondary data obtained from the websites of the World Bank, BPS, and OECD is utilized in this study. Data testing uses a data panel regression analysis model with Eviews 10 software. The results of this study indicate that Foreign Direct Investment and inflation have a significant positive effect on economic development. Conversely, the environmental degradation has a significant negative impact on economic growth. The findings of this study confirm that economic growth can be enhanced through increasing FDI inflows, maintaining a stable inflation rate, and environmental degradation at a certain level, which can stimulate economic growth. Therefore, all variables in this study contribute to economic growth.